Specific localisation of ions in bacterial membranes unravels physical mechanism of effective bacteria killing by sanitiser - Thoma, Judith; Abuillan, Wasim; Furikado, Ippei; Habe, Taichi; Yamamoto, Akihisa; Gierlich, Simone; Kaufmann, Stefan; Brandenburg, Klaus; Gutsmann, Thomas; Konovalov, Oleg; Inoue, Shigeto; Tanaka, Motomu (Scientific reports, 2020)
Antimicrobial resistance is a major threat to public health. Although many commercial sanitisers contain a combination of cationic surfactants and aromatic alcohols, the physical mechanisms where these two substances bind to or how they disturb bacterial membranes are still largely unknown. In this study, we designed a well-defined model of Gram-negative bacteria surfaces based on the monolayer of lipopolysaccharides with uniform saccharide head groups. Since commonly used X-ray reflectivity is sensitive to changes in the thickness, roughness and electron density but is not sensitive to elements, we employed grazing incidence X-ray fluorescence. In the absence of Ca2+, cationic surfactants can penetrate into the membrane core with no extra support by disturbing the layer of K+ coupled to negatively charged saccharide head group at z = 17 Å from the air/chain interface. On the other hand, Ca2+ confined at z = 19 Å crosslink charged saccharides and prevent the incorporation of cationic surfactants. We found that the addition of nonlethal aromatic alcohols facilitate the incorporation of cationic surfactants by the significant roughening of the chain/saccharide interface. Combination of precise localisation of ions and molecular-level structural analysis quantitatively demonstrated the synegtestic interplay of ingredients to achieve a high antibacterial activity.
Gesehen am 05.10.2020